Comparison between Mobile Camera and DSLR Camera Photography for the Evaluation of Shade of Anterior Teeth - A Cross-Sectional Study - Shrestha, Prabhat; Poudel, Sabina (Journal of Chitwan Medical College, 2019)
Background: Color accuracy plays a major role in creating an esthetic prosthesis. Photos taken with DSLR cameras have been the most frequent means of recording and transferring the color of teeth. Mobile phone cameras are emerging as a popular alternative to DSLR cameras due to its convenience. Our aim was to compare the color difference (ΔE) between the pictures taken with DSLR cameras and mobile cameras with and without using flash.Methods: Photos of right maxillary central incisors of patients (n=60) were taken with DSLR camera and mobile camera with and without using flash. The pictures were standardized with gray card and processed in Adobe Photoshop Lightroom CC software and the L*a*b* values of the pictures were compared to find the difference in color.Results: The percentage of agreement (ΔE≤2.7) for the difference of color between DSLR camera and mobile phone cameras without using flash (ΔE1) was 3.3% and with using flash (ΔE2) was 1.7%. The coefficient of agreement (using Kappa coefficient) between (ΔE1) and (ΔE2) showed total disagreement (kappa value =-.02). The mean values of ΔE1 was (8.3±3.3) and ΔE2 was (7.23±2.4).Conclusions: It was concluded that the color of mobile camera with or without using flash could not be considered as an acceptable method of recording color of teeth.